Pengaruh Pengawasan dan Lingkungan Kerja Terhadap Semangat Kerja Pegawai pada Dinas Lingkungan Hidup Kota Bima - Hasan, Sahrul; Rahmatia, Rahmatia; Kusumayadi, Firmansyah (Jurnal Serambi Ekonomi dan Bisnis, 2024)
The purpose of this research is to determine and analyze the influence of Supervision and the Work Environment partially or simultaneously on Employee Work Morale at the Bima City Environmental Service. This type of research is associative research. The research instrument uses a questionnaire which is measured using a Likert scale. The population used was all employees at the Bima City Environmental Service, 46 people. For 30 ASN employees and 16 honorary employees, the sample in this study was 30 ASN employees. The sampling technique used is proportional sampling. Data collection techniques are observation, questionnaires and literature study. Data analysis uses validity tests, reliability tests, multiple linear regression tests, correlation coefficient tests, determination tests, t tests and tests. The research results show that supervision and the work environment have a partial or simultaneous effect on employee morale at the Bima City Environmental Service.